PENGARUH LATIHAN PLYOMETRIC SKIPPING DAN SPLIT JUMP TER-HADAP HASIL KECEPATAN LARI SPRINT 60 METER UNTUK PESERTA EKTRAKURIKULER USIA 15-17 TAHUN DI SMAN 1 TUREN - Riza Thoyibatul Ummah; Slamet Raharjo; Sapto Adi (Jurnal Sport Science, 2016)
Abstract: This research has purposes to determine differences in the effects of exercise plyometric jump skipping and split with conventional exercise on the results of running speed sprint 60 meters at students aged 15-17 years in SMAN 1 Turen. The same subject within these divisions is done by ordinal matching pairing with two groups: the ex-perimental and conventional as a comparison group. Samples of the research is senior high school (SMAN 1) Turen. From the Anova test results showed that the Sig. <α , ie 0.002 <0.05 which means that H0 is rejected. The difference can be seen with the ex-perimental group of Fhitung 11,599 > 4,20 Ftabel, concluded that there is significant in the experimental groupplyometric skipping and split jump.Keyword: exercise plyometric skipping and split jump, speed.